Pengaruh Ulasan Produk, Kepercayaan dan Harga terhadap Keputusan Pembelian Produk Kecantikan di Marketplace Shopee - Setyaningrum, Vira; Pebrianggara, Alshaf; Indayani, Lilik (Universitas Batanghari Jambi, 2025)
This research aims to determine the influence of product reviews, trust, and price on purchasing decisions for beauty products on the Shopee Marketplace. This research is a quantitative study with data obtained from distributing questionnaires which were measured using the Linkert scale. The sample in this study amounted to 96 people with a sampling technique, namely the purposive sampling method. The results of this research conclude that there is a positive and significant influence between the product review, trust and price variables on the decision to purchase beauty products on the Shopee marketplace, both simultaneously and partially.